Detection of Concurrency Errors in Multithreaded Applications Based on Static Source Code Analysis - Damian Giebas; Rafal Wojszczyk (IEEE Access, 2021)
Computer systems that allow multithreaded execution of applications have become extremely common, even small portable devices operate in multithreaded mode. This is undoubtedly very convenient for users, but for programmers it is associated with many unwanted errors, which can occur after writing application code. These errors include race condition, deadlock, atomicity violation and order violation. The subject of this work is related to the detection of these errors in the process of static software analysis. The paper presents the author’s model, which was then used to detect the above-mentioned occurrences, additionally each error has been discussed in detail. A tool supporting the detection of errors in multithreaded applications was also developed and the results of this tool were presented.